Uma análise dialógica da argumentação na tentação de Jesus em Mateus 4:1-11 - Silva, Fagner Carvalho (2023)
The temptation of Jesus is a millennial text that challenges the imagination of many Christians. The temptation originally belonged to a material known as Source Q.So the Gospel of Luke is the work that kept the closest form to the original. This study adopted as corpus the temptation of Jesus materialized in the Gospel of Matthew (chapter 4:1-11). First, because the temptation of Jesus in Matthew is little discussed, even though there are finishing elements that make it different from the materialization in Luke. Not least, the temptation in Matthew reveals a veiled controversy that is when the discourses conveyed by the characters Jesus and The Devil are submitted to the dialogical analysis of the argumentation. In the light of this analytical method developed by Nascimento (2018), this study aims to demonstrate the positions of the characters in the polemical literary event of temptation in Matthew 4:1-11. Thus, we seek to understand the functioning of the controversy, whether it is open or veiled. The dialogical analysis of argumentation is the epistemological encounter between Bakhtinian philosophy and the New Rhetoric of Chaïm Perelman and Lucie Olbrechts-Tyteca. Four hypotheses arise from this meeting. The first hypothesis is that polemic is a veiled hatred of the other’s beloved values, manifesting itself argumentatively by the polarization, whose particular characteristics are delineated in the concrete argumentative process. The second hypothesis is that the polemical event is the meeting of positions, founding snares of two antagonistic discursive fields, responsible for updating entities of other controversies in a given chronotope. The third hypothesis is that polemical acts are argumentative strategies, positions and arguments, through which it is possible to observe a certain memory update. The fourth and last hypothesis is the notion of a controversial micro act. Considering these hypotheses, in particular the notion of a polemical event, we propose the notion of a polemical literary event that can be understood as the simulation of a controversy in which discourses are conveyed by characters representing antagonistic positions in a given chronotope. From we discuss the possibility of a dialogical and argumentative analysis of temptation as discursive genre; we seek to identify the elements that evidence the functioning of the discursive memory (polemic) in the construction of meaning and in the resumption of this memory; we investigate how the positions in the antagonistic discourses are constituted, as well as the chronotope in temptation. The results point to the construction of an open polemic between the characters, but, above all, a veiled controversy, a veiled clash, between the community of Matthew, whose discourse is conveyed by the character Jesus, and Judaism whose discourse is conveyed by the character Devil.